Hydrocarbon microseepage-based remote sensing analysis in the Biru Basin-China - Jindong Cui; Hui Xu (Discover Applied Sciences)
Abstract To unlock the vast yet environmentally sensitive, untapped oil and gas resources in the Tibetan region of China, a study was conducted within the Biru Basin utilizing remote sensing technology grounded in hydrocarbon microseepage theory. The research overlapped remote sensing-derived oil and gas information with recognized areas exhibiting hydrocarbon microseepage and related anomalies. Various analytical techniques were applied, such as band ratio calculations, multispectral band fusion, and Principal Component Analysis, specifically focusing on the hydroxyl/iron spectral signature. The results indicated a strong positive correlation between the identified zones of hydrocarbon microseepage anomalies and known occurrences of oil and gas shows. Conversely, a spatial superposition of these anomaly zones onto the established oil reservoirs in the Lunpola Basin revealed an inverse relationship, suggesting that regions devoid of hydrocarbon microseepage anomalies could potentially host petroliferous deposits. These methodologies precisely defined the boundaries of hydrocarbon microseepage non-anomalous zones, identifying a primary area without such anomalies. By integrating essential basin-scale geological elements, including source rock distribution, reservoir presence, cap-rock properties, and trap configurations, One favorable block for oil and gas exploration has been identified, specifically the area east of Biru-bianba, which covers over 1000 km². Consequently, this area has been designated as a high-priority target for future oil and gas exploration initiatives.